Survey conducted among Medical and Social Sciences students on body donation for research and teaching purposes - Ciliberti, Rosagemma; Bonzano, Chiara; Petralia, Paolo; Lalli, Luca; Licata, Marta; Manti, Franco; Bonsignore, Alessandro (Medicina e Morale, 2021)
The recent Italian Law 10 February 2020, n. 10 "Rules on the disposition of one’s own body and post mortem tissues for study purposes, training and scientific research" aims to enhance the voluntary nature of body donation. In this context, the ethical debate on body donation and its profound meaning, which relates beneficence to a relational vision of autonomy, becomes relevant. At the same time, the strong symbolic value attributed to the body cannot be overlooked. The practical implementation of body donation, therefore, requires a broad training strategy, capable of developing the assumption of responsibility with respect to the present and future generations. In consideration of the important role that physicians, health and social professions can play in promoting such a practice, a survey aimed to explore the knowledge and beliefs, existing in this area, among the students belonging to the School of Medical and Pharmaceutical Sciences (SMF) and those attending the School of Social Sciences (SSS), as well as to analyse any factors that may influence body donation, was conducted. The survey highlighted important information and training gaps on issues related to care, donation and respect for people. These criticalities are particularly significant between students belonging to the SMF who, as future physicians, will be able to constitute a fundamental reference for the spread of body donation. Investing economic and intellectual resources on students’ ethical competence can be a very important factor for body donation to be configured as a responsible, conscious, and effectively practiced choice.